2001
DOI: 10.1080/01421590120057067
|View full text |Cite
|
Sign up to set email alerts
|

Identifying undergraduate medical students' attitudes towards communication skills learning: a pilot study

Abstract: Research shows that students' conceptions of what 'learning' is influences both their approaches to learning and their learning outcomes. Lower level conceptions of learning are associated with surface approaches to learning, encouraging poor quality learning outcomes. However, more advanced conceptions are associated with deep learning approaches and high-quality learning outcomes. The Structure of Observed Learning Outcomes (SOLO) taxonomy was used to analyse the conceptions of learning of a new intake of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
42
7
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 7 publications
7
42
7
6
Order By: Relevance
“…The results of this study revealed that there were significant differences between the two groups of participants in their positive as well as negative attitudes towards communication skills. The results are in accordance with previous studies suggesting that more mature students have higher positive attitudes and lower negative attitudes towards communication skills compared to students at the beginning of their undergraduate studies (Shankar et al, 2010;Ihmeideh et al, 2010;Rees & Garrud, 2001 Vol. 10, No.…”
Section: Resultssupporting
confidence: 92%
“…The results of this study revealed that there were significant differences between the two groups of participants in their positive as well as negative attitudes towards communication skills. The results are in accordance with previous studies suggesting that more mature students have higher positive attitudes and lower negative attitudes towards communication skills compared to students at the beginning of their undergraduate studies (Shankar et al, 2010;Ihmeideh et al, 2010;Rees & Garrud, 2001 Vol. 10, No.…”
Section: Resultssupporting
confidence: 92%
“…The CSAS was developed by Rees et al (2002a). Female medical students seem to have more positive attitudes than males to learning communication skills (Rees & Rees & Garrud (2001) Qualitative study to explore medical students' views and experiences of CSL First-year medical students (N ¼…”
Section: Introductionmentioning
confidence: 99%
“…3 However, negative attitudes towards learning communication skills are common, as students do not recognize the training of communication skills as an important part of academic education and medical practice, or do not perceive a need to improve their own skills. [4][5][6][7][8] Several variables are assumed to affect attitudes towards communication skills training, e.g. the appreciation of patient-oriented care.…”
Section: Introductionmentioning
confidence: 99%